Cytokine-stimulated T cells induce macrophage IL-10 production dependent on phosphatidylinositol 3-kinase and p70S6K: implications for rheumatoid arthritis. - Foey, A; Green, P; Foxwell, B; Feldmann, M; Brennan, F (2002)
IL-10 is an anti-inflammatory cytokine produced in the joint in rheumatoid arthritis by macrophages and infiltrating blood lymphocytes. Regulation of its expression is poorly understood, but previous findings have suggested that physical interactions with T cells may play a role. This report investigates signalling mechanisms involved in the production of macrophage IL-10 upon interaction with fixed, cytokine-stimulated T cells (Tck). Elutriated monocytes were differentiated to macrophages by macrophage-colony-stimulating factor (M-CSF) and co-cultured with fixed T cells chronically stimulated in a cytokine cocktail of IL-2/IL-6/tumour necrosis factor (TNF)-alpha in the presence or absence of wortmannin and LY294002, inhibitors of phosphatidylinositol 3-kinase (PI3K), or of rapamycin, an inhibitor of p70 S6-kinase (p70S6K). Spontaneous IL-10 production by rheumatoid arthritis synovial-membrane mononuclear cells (RA-SMCs) and co-cultures of rheumatoid arthritis T cells (RA-Ts) and macrophages was also assessed. RA-T and Tck induction of macrophage IL-10 production was suppressed by cell separation and inhibition of PI3K and p70S6K. PI3K involvement was also shown by phosphorylation of the downstream effector protein kinase B. Spontaneous IL-10 production by RA-SMCs was also inhibited by LY294002 and depletion of the nonadherent (T-cell-enriched) fraction of the cell population. IL-10 production in RA-SMCs and M-CSF-primed macrophages, activated by interaction with Tck, is PI3K- and p70S6K-dependent.